Análisis de la aplicación de la comunicación digital en la Universidad Técnica de Babahoyo para divulgación de información social, cultural y eventos - López Gómez, Fabiola Elizabeth (2020)
This research analyzes the efficiency of the application of digital communication, on the official website of the Technical University of Babahoyo (UTB) within the social network Facebook, on issues of dissemination of social, cultural information and events, since for this a qualitative and quantitative design was used through diagnostic and descriptive research, through the techniques of collecting surveys, interviews and direct observation. Where the students of the eighth semesters of the Faculty of Legal, Social and Educational Sciences were surveyed, specifically within the careers of Social Communication, Hospitality and Tourism, Clinical Psychology and Basic Education, through a questionnaire of 6 closed questions. Likewise, the person in charge of the communication area of the UTB was interviewed. These results showed that the aforementioned alma mater is well aimed at taking advantage of and being part of the digital era